COVID-19 Pandemic: Socio-Economic Consequences of Social Distancing Measures in Italy - Auriemma, Vincenzo; Iannaccone, Chiara (Frontiers in Sociology, 2020)
The lock-down measures adopted in all countries of the world have led to far-reaching social and economic changes. The health emergency had immediate repercussions on the social system first and then on the economic system. The social repression measures taken to limit the infection have generated a drastic change in our daily life, detaching ourselves from the other emotionally and physically. The already difficult situation that Italy was experiencing from an economic and social point of view is immediately exposed by the health emergency, and then worsened and extended to all sectors. In this context, it is important to study different types of phenomena: the suspension of commercial activities and the consequent repercussions on the work sector, smart-working and infrastructural and cultural digital divide, the new forms of interaction and relationship that transform the emotions and, finally, the enormous fluctuation of world markets. To face such a far-reaching crisis, the measures taken not only at national level, but also supranational and international will be decisive.